A comparative study in the application of the natural justice principles in courts of law and student's tribunals in Malaysia / Ahmad Feisai Mohd Azmi … [et al.] - Mohd Azmi, Ahmad Feisal; Mohd Jeffery ong, Harris Ong; Johari, Hafiza; Jalal, Junaidah (Faculty of Law, 2005)
Lord Denning once said, "When a man's reputation or livelihood is at stake, he not only has a right to speak with his own mouth but also has a right to speak by counsel or solicitor. The principles of natural justice are very important to be observed in our legal system against the abuse of power by the authority. The main objective of this project paper is to make a comparative study in the application of natural justice principles in the Courts of Law and student's tribunals in Malaysia. During the course of this study, several relevant and reliable sources may be referred to. These sources including legal materials such as statutes, case law, law report and books. Interviews will be conducted with both, lecturers and students in UiTM. It is hoped that at the end of this study, a better understanding concerning natural justice principles in student's tribunals could be gained by everyone. Eventually, we would also like to put forward our proposition that the principles of natural justice should be properly observed in the student's tribunals as in the Courts of Law.